2004
DOI: 10.1097/01.ju.0000135530.59860.7d
|View full text |Cite
|
Sign up to set email alerts
|

Partial Cystectomy: A Contemporary Review of the Memorial Sloan-Kettering Cancer Center Experience and Recommendations for Patient Selection

Abstract: In highly selected patients with invasive bladder cancer, partial cystectomy offers acceptable outcomes. Concomitant CIS and presence of metastases to regional lymph nodes predict advanced recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
110
2
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(126 citation statements)
references
References 17 publications
4
110
2
10
Order By: Relevance
“…Studies have shown that, in carefully selected patients with small, solitary primary tumours at the dome or posterolateral wall of the bladder, PC can be a reasonable alternative to RC because PC allows radical excision of the tumour with comparably less morbidity and preservation of urinary and sexual functions. [3][4][5][6] In our study, the local recurrence rate was 30.7%, comparable with contemporary series reporting local recurrence rates of 19-35%. 3,4 Treatment delays in bladder cancer patients Invasive bladder tumours are aggressive from the time of presentation, suggesting that delaying treatment for such cancer may lead to a worse outcome.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Studies have shown that, in carefully selected patients with small, solitary primary tumours at the dome or posterolateral wall of the bladder, PC can be a reasonable alternative to RC because PC allows radical excision of the tumour with comparably less morbidity and preservation of urinary and sexual functions. [3][4][5][6] In our study, the local recurrence rate was 30.7%, comparable with contemporary series reporting local recurrence rates of 19-35%. 3,4 Treatment delays in bladder cancer patients Invasive bladder tumours are aggressive from the time of presentation, suggesting that delaying treatment for such cancer may lead to a worse outcome.…”
Section: Discussionsupporting
confidence: 75%
“…studies have demonstrated that for a highly select patient population, a partial cystectomy (PC) may offer comparable cure rates to RC. 3,4 Ideal candidates for PC are those with favourable disease characteristics such as small, solitary, primary tumours amenable to surgical resection with 2-cm margins, without the need for ureteral reimplantation. 5,6 Even though treatment for invasive bladder cancer should be preferably initiated as soon as the diagnosis has been made, delays in providing such treatment can sometimes be unavoidable owing to factors related to the patient or health care system.…”
Section: Discussionmentioning
confidence: 99%
“…219 The presence of CIS on an initial TURBT or in the partial cystectomy specimen and the presence of lymph node involvement significantly predict tumor recurrence, and patients with these findings should be considered poor candidates for partial cystectomy. 220 …”
Section: Bladder Preservationmentioning
confidence: 99%
“…Parsiyel sistektomi sırasında cerrahi sınırın pozitif olması, CIS varlığı ve çok sayıda tümör olması izlemde nüks olasılığını arttırmaktadır. CIS ve çok odak mevcudiyeti yü-zeyel nükslerle olan ilişkisinin istatistiksel olarak anlamlı olduğu, lenf nodu tutulumu ve cerrahi sınır pozitifliğinin ise ileri nükslerle bağlantılı olduğu saptanmıştır (11). Olgumuzda hem CIS olmayışı, hemde lenf nodu metastazının olmayışı, operasyon öncesi ve sonrası takiplerinde mesane dışı yayılım olmaması gerek nüks, metastaz gerekse sürvi konusunda olumlu parametreler olsada tümörün natürüde göz önüne alındığında sarkomatoid-lenfoepitelyoma diferansiye mesane tümörleri gibi agresif yapıda tü-mörler için parsiyel sistektominin sürvisi konusunda literatürdeki bilgilerde oldukça kısıtlıdır.…”
Section: Discussionunclassified